Stored grain compaction factor: accurate factors are necessary because volume measurements will not give exact measure of grain - Bhadra, Rumela (My University, 2014)
It is well known that grain undergoes compression when subjected to cumulative weight exerted from the overlying material in a storage unit. The extent of compression depends on several factors associated with the stored materials (crop type, test weight, moisture content) and bin characteristics (type of bin wall material, size and geometry of the grain bin). Compression of grain leads to packing and thus adjusts the bulk density of the material. Therefore, accurate compaction factors are necessary, because volume measurements of the stored grain alone will not allow us to determine the exact amount of grain in the bin.
Keywords: Stored grain; Compression; Volume